Analysis of Social and Ecological Market Economy (SEME) Concept on Tourism Village: Lembur Cigarukgak Case Study - Asep Kurniawan (JASS (Journal of Accounting for Sustainable Society), 2026)
The global tourism industry is experiencing a paradigm shift toward the Wellness Economy, as travelers increasingly seek regenerative experiences in rural settings. This study examines the implementation of the Social and Ecological Market Economy (SEME) framework within the Lembur Cigarukgak tourism village in Sidajaya, Subang, West Java. By analyzing the governance model of BUMDes Wira Usaha Sejahtera, this research investigates how the integration of market freedom, social equity, and ecological integrity functions as a driver for sustainable rural development. Utilizing a qualitative case study approach with data derived from institutional profiles, financial reports, and in-depth informant interviews, the findings demonstrate that Sidajaya’s model of "SEME-Wellness Zones" creates an antifragile rural economy. The model operationalizes communal ownership, where 60-70% of profits are reinvested locally, ensuring that economic gains from tourism are not extracted by external urban actors. Furthermore, the synergy between digital infrastructure—the Cigarukgak Network—and low-impact wellness tourism highlights a successful synthesis of modern innovation and traditional values. The study concludes that the Sidajaya prototype effectively safeguards the village's Maqasid al-Shariah—life, faith, and wealth—and offers a scalable model for poverty relief and ecosystem rebirth in rural Indonesia.